The Role of Nutrition in Cardiometabolic Health Experimental, Clinical, and Community-Based Evidence - Mahmoud, Abeer M.; Phillips, Shane (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The purpose of this Special Issue "The Role of Nutrition in Cardiometabolic Health: Experimental, Clinical, and Community-Based Evidence" is to publish a focused, coherent, impactful, and well-cited volume on how nutrition influences diverse cardiometabolic risk factors. Cardiometabolic diseases, such as coronary heart disease, stroke, type 2 diabetes mellitus, and obesity, is the leading cause of death worldwide. In recent years, dietary habits have shifted all over the globe. At the same time, a constantly growing body of evidence demonstrates the role of caloric intake and dietary composition as determinants of cardiometabolic health. Suboptimal diet predisposes to a myriad of cardiometabolic risk factors such as impaired glucose metabolism, insulin resistance, dyslipidaemias, and high blood pressure.